Finding psychopaths in white-collar jobs: a review of the evidence and why it matters. Issue 2 (30th August 2021) - Boddy, Clive Roland; Taplin, Ross; Sheehy, Benedict; Murphy, Brendon
Abstract : Purpose: Influential research has posited that empirical investigation provides no evidence for the existence of white-collar/successful psychopaths. The purpose of this current paper is to review evidence for their existence and report on new, primary research that examines ethical outcomes associated with their presence. Design/methodology/approach: Leading psychopathy researchers called for research using samples of white-collar workers to explore workplace psychopathy. Therefore, the authors undertook a two-stage research process to examine this. Firstly, a structured literature review sought evidence for "corporate psychopaths", "white-collar psychopaths" and "successful psychopaths" in existing literature. Secondly, original research was undertaken among 261 Australian workers to examine this further. Findings: Findings indicate that white-collar psychopaths exist. Where they have been found not to exist, investigation reveals that the samples used were inadequate for the purpose of attempting to find them. Practical implications: Although there is an inconsistent nomenclature, white-collar, industrial, successful, organisational, workplace or corporate psychopaths do exist and are found in white-collar workplaces. Social implications: Their existence is important because findings indicate that they have a significant, ethically malign and long-lasting impact on employee well-being and organisational ethical outcomes. Originality/value: To the best of the authors' knowledge, this is perhaps the first paper to specifically examine the literature for evidence of whether white-collar psychopaths exist. To the best of the authors' knowledge, this is also the first paper to determine that corporate psychopaths are linked with aggressive humour, gender discrimination, fake corporate social responsibility and reduced communications integration.